Pemilihan Umum Serentak Tahun 2024 Berdasarkan Putusan Mahkamah Konstitusi Republik Indonesia - Cecep Prayatno; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2023)
General elections (Pemilu) are an election process involving all citizens who will use their voting rights to elect their representatives. The Court considers that the implications and implementation of holding elections are not solely caused by the choice of electoral system. In this case, if in the future improvements will be made to the current system, legislators must consider several things, including, namely, not making changes too often, changes are made in order to perfect the electoral system, changes must be made early before When the election implementation stage begins, it is still necessary to maintain balance and continuity between the roles of political parties. as stated in Article 22E paragraph (3) of the 1945 Constitution and the principle of popular sovereignty as stated in Article 1 paragraph (2) of the 1945 Constitution, involving all groups who have an interest in the implementation of elections by applying the principle of meaningful public participation. Approaching the final deadline for registration of presidential and vice presidential candidates, the public was shocked by the decision of the Constitutional Court (MK) which was considered controversial number 90/PUU-XXI/2023. In this decision, the Constitutional Court decided that regional heads under the age of 40 can nominate themselves as presidential or vice presidential candidates. The main issues in this journal are the Constitutional Court's decision regarding the 2024 general election and the Constitutional Court's decision regarding the age of the Presidential Candidates. and Cawapres. The research used is normative juridical research which is qualitative in nature, where normative juridical research refers to the laws contained in applicable laws and regulations and norms existing in society where the research sources are taken from books, regulations. legislation, expert opinions and supporting matters in normative research. From the results of this research, the Constitutional Court Decision Number 90/PUU-XXI/2023 which states that Article 169 letter q of Law Number 7 of 2017 concerning General Elections which states